2020
DOI: 10.1177/2151459319898646
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Expedite Surgical Hip Fracture Care

Abstract: Introduction: In 2014, we implemented a geriatric hip fracture patient care pathway at our institution which was designed to improve outcomes and decrease time to surgery. Materials and Methods: We analyzed retrospective data from 463 patients, aged greater than 50, who had surgical treatment for a closed hip fracture due to a low-energy injury between 2013 and 2016 at an academic institution. Objective outcome measures included time to surgery, mortality rate, and total hospital length of stay. Our primary go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…12 When we looked at our own trauma institution to determine how to improve outcomes, our findings shared similarities with other studies. Friedman et al, 20 Christiano et al, 16 and Burton et al 17 reported improved outcomes in geriatric patients with hip fracture after implementation of a protocol, which further highlights the importance of protocol-driven care. They showed that expedited surgical care improved time to surgery from 20.22 to 15.33 hours but did not show a difference in-hospital length of stay or mortality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…12 When we looked at our own trauma institution to determine how to improve outcomes, our findings shared similarities with other studies. Friedman et al, 20 Christiano et al, 16 and Burton et al 17 reported improved outcomes in geriatric patients with hip fracture after implementation of a protocol, which further highlights the importance of protocol-driven care. They showed that expedited surgical care improved time to surgery from 20.22 to 15.33 hours but did not show a difference in-hospital length of stay or mortality.…”
Section: Discussionmentioning
confidence: 98%
“… 16 Others have introduced a multidisciplinary approach that resulted in a 10% improvement in the percentage of patients having surgery within 24 hours. 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS 33,35,38,41,[43][44][45][46][47][48][49][51][52][53][54]56,57,[59][60][61][62][65][66][67][68][69][70][71][72][74][75][76][79][80][81][82][85][86][87][88]91,94,96,97,99,101,103 and 20 programs 39,40,42,50,…”
Section: Included Studiesmentioning
confidence: 99%
“…There are numerous factors upsetting patient satisfaction: attainment attention from doctors, time taken to get schedule, opening hours, waiting time, expenses, expediency, treatment quality, pain management, and nurse communication [21]. The literature on patient satisfaction with primary care show that key attributes of healthcare treasured by patients are patient-centered, as well as time spent with the physician, willingness of the physician to listen to the patient, and expectations for treatment [9,22].…”
Section: Factors Upsetting Patient Satisfactionmentioning
confidence: 99%